The Influence of Harvesting Period on Lipid Associated Antioxidant Activity of Semicontinuously Grown Chlorella vulgaris - Tjandara Chrismadha; Diani Sartika; Iriani Setyaningsih; Uju Uju (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
A green alga, Chlorella vulgaris was grown semi-continuosly at various harvesting periods, and the lipid content and its associated antioxidant activity was examined. The harvesting periods were 9, 18, and 27 days, while the algal culture was placed in 10 L glass bottles provided with aeration for gas exchange and mixing. Light was obtained from 440 watt cool fluorescent lamps placed at one side of the culture. Room temperature was 26-32C. Algal lipid extraction was done based on liquid phase separation of methanol :chloroform:water and the antioxidant activity was examined by means of oxidation inhibitory in ethanol emulsified limnoleic acid. In addition, a TLC analysis was performed to identify the antioxidant compouns soluble in the lipid. The results showed that harvesting per iod had a significant influence on the algal lipid content, which were 11.94, 12.96, and 16.51% of the dry weight in the culture with harvesting periods of 9, 18, and 27 days, respectively. No remarkable effect of the harvesting period on the antioxidant activity, which were observed to inhibit oxidation of linoleic acid up to 67-71%. There were five compounds found can be associated with the algal antioxidant activity, which were pheophorbide -a, chlorophyll-b,chlorophyll-a, phaeophytin-a, -carotene, and an unidentified one. Key words: microalgae, Chlorella vulgaris, lipid, antioxidant, harvesting period